2018
DOI: 10.1007/s11764-018-0693-9
|View full text |Cite
|
Sign up to set email alerts
|

An online randomized controlled trial, with or without problem-solving treatment, for long-term cancer survivors after hematopoietic cell transplantation

Abstract: Online and telehealth programs such as INSPIRE offer opportunities to enhance HCT survivorship outcomes, particularly for mood, though methods would benefit from strategies to improve efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
106
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 63 publications
(107 citation statements)
references
References 82 publications
1
106
0
Order By: Relevance
“…The trials were published between 2005–2018. Trials were undertaken in the USA (Bantum et al, ; Owen et al, ; Smith et al, ; Somers et al, ; Syrjala et al, ), Netherlands (Admiraal et al, ; van der Berg et al, ; Boele et al, ; Golsteijn et al, ; Willems et al, ), UK (Foster et al, ), Canada (Vallerand et al, ), China (Zhang et al, ; Zhu et al, ), and South Korea (Lee et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The trials were published between 2005–2018. Trials were undertaken in the USA (Bantum et al, ; Owen et al, ; Smith et al, ; Somers et al, ; Syrjala et al, ), Netherlands (Admiraal et al, ; van der Berg et al, ; Boele et al, ; Golsteijn et al, ; Willems et al, ), UK (Foster et al, ), Canada (Vallerand et al, ), China (Zhang et al, ; Zhu et al, ), and South Korea (Lee et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Participants in four trials were patients with any cancer (Foster et al, ; Bantum et al, ; Somers et al, ; Willems et al, ). The other eleven trials focused on specific cancers: breast cancer (Admiraal et al, ; van den Berg et al, ; Lee et al, ; Owen et al, ; Smith et al, ; Zhu et al, ), glioma (Boele et al, ), haematological cancer (Syrjala et al, ; Vallerand et al, ), rectal cancer (Zhang et al, ), and both colorectal cancer and prostate cancer (Golsteijn et al, ). Nine trials reported participants who completed primary treatment (Admiraal et al, ; van der Berg et al, ; Foster et al, ; Lee et al, ; Bantum et al, ; Somers et al, ; Syrjala et al, ; Willems et al, ; Zhang et al, ); the time since treatment completion was 4 weeks to 18 years.…”
Section: Resultsmentioning
confidence: 99%
“…Although program use was greater for HCT survivors with moderate distress and with a trend for those with moderate comorbidities, other programs have found that healthier survivors with less potential to benefit are more likely to enroll in and engage in online programs [33]. For the INSPIRE RCT, participants viewing 2+ pages were more likely to report improved depressive symptoms with a trend toward improved distress [34]. Our results suggest that survivors with severe mental or physical health problems require additional strategies beyond open access online interventions, both to engage them and to improve their outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Although online modalities may not meet the needs of all survivors and may be used more often by those with moderate needs compared with those with severe needs or no needs, most of those participating in the INSPIRE program used the site. Although we note that the reported analyses were not designed to test whether the INSPIRE program had a positive effect on survivorship outcomes, the primary analysis of the clinical trial indicated that engagement is important to improved outcomes [34]. Additional outreach methods are needed for those who have more severe late effects or who do not respond to online interventions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation